Lateral-Torsional Buckling of Wide Flange Cantilever Beams - Dowswell, Bo (Engineering Journal, 2004)
The American Institute of Steel Construction, Load and Resistance Factor Design Specification for Structural Steel Buildings includes provisions for the design of beams to prevent lateral-torsional buckling. The design method uses an equation that was derived for a simply supported beam with equal end moments. The equation is not accurate for cantilever beams because the mechanics of buckling are different from simply supported beams. The AISC procedure produces over-conservative results for cantilever beams that are braced laterally at the tension flange, and unsafe results for cantilever beams that are braced laterally at the compression flange. Equations to predict the lateral-torsional buckling capacity of cantilever beams were developed by curve fitting elastic finite element data from the program BASP. The equations explicitly account for the effects of bracing, load height, and moment distribution along the length of the beam. Simplified equations are proposed that are generally conservative compared to the finite element data. A design method is proposed that uses a modified factor to be used with the AISC procedure.